THE PARAMETRIC REPRESENTATION OF THE SPACE $b_α^2$ OF HARMONIC FUNCTIONS - Petrosyan, A. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In the paper the parametric representation for Hilbert spaces $b_α^2(B)$ of functions harmonic in the unit ball $B\subset \mathbb R_n $ is obtained.
Keywords: Hilbert spaces; unit ball; parametric representation